AB0447 Comparison of efficacy of four biological agents for rheumatoid arthritis patients using the HRQOL questionnaire and depression scale. (23rd January 2014) - Miwa, Y.; Furuya, H.; Yanai, R.; Ohtsuka, K.; Sato, M.; Takahashi, R.; Wakabayashi, K.; Yajima, N.; Kasama, T.; Hosaka, M.
Abstract : Background: Health-related quality of life (HRQoL) as a patient-reported outcome in rheumatoid arthritis (RA) has become an important tool in the clinical evaluation of patient preferences and perceptions of individual health. Objectives: The objective of this study was to compare the validity of the HRQoL with respect to depression in RA patients treated with infliximab, etanercept, adalimumab or tocilizumab. Methods: One hundred seven RA patients (infliximab, 47 pts; etanercept, 17 pts; adalimumab, 25 pts; tocilizumab, 18 ptts) were assessed prior to treatment and again at 30 weeks after initiation of therapy. The age, gender, and steroid dosage were obtained for each participant, and the HRQoL questionnaire (modified health assessment questionnaire (mHAQ) and Short Form (SF)-36) and depression scale (Japanese version of the structured interview guide for the Hamilton Depression rating scale (HAM-D) and the Self-rating Depression Scale (SDS)) were administered to patients. The primary endpoint was the assessment of clinical improvements, and the secondary endpoints were assessments of the changes in the HRQoL and depression scale. Results: After 30 weeks of treatment, the DAS28 score of patients treated with tocilizumab was lower than the score of patients treated with adalimumab (p<0.05). There were no significant differences in the percentage of low disease activity and remission. Although no significant differences were found for the HAM-D and SDS scores, the changes in the scores of the mHAQ—role physical, body pain, vitality, social function, role emotion and mental health—as measured by the SF-36 differed significantly between the four groups. Specifically, etanercept treatment was associated with significant improvement as measured by HRQoL compared with adalimumab and tocilizumab therapy. However, there were no significant differences with respect to age, gender, steroid dosage, DAS28 (before treatment) and physical function and general health as measured by the SF-36. Conclusions: In this study, etanercept treatment was associated with a significant improvement in many items of the HRQoL evaluation compared with other drugs, without taking into account the efficacy of drug. Although mental health as measured by the SF-36 was improved, the HAM-D and SDS scores did not differ between the four groups. Disclosure of Interest: Y. Miwa Grant/Research support from: tanabemitsubishi, wyeth, abott, eizai, chugai, bristol, H. Furuya: None Declared, R. Yanai: None Declared, K. Ohtsuka: None Declared, M. Sato: None Declared, R. Takahashi: None Declared, K. Wakabayashi: None Declared, N. Yajima: None Declared, T. Kasama: None Declared, M. Hosaka: None Declared